Perbandingan Teologi Keselamatan Antara Katolik Dan Protestan Sebelum Dan Sesudah Gerakan Reformasi - Marde Christian Stenly Mawikere (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2017)
Marde Christian Stenly Mawikere, Salvation theological comparison between Catholic and protestant before and after reform. This article is an overview of comparative theology Safety bet-ween Catholics and Protestants Before and After Reform based review of the literature has been provided. Departing from the historical context of the socio-religious Europe since the 5th century to 1517 which shows the blend between philosophy and theology of the church led to deviate from the teachings of the Bible. The situation Christianity and medieval zeitgeist called dark ages of the church which fueled the Protestant reform movement. The Protestant reform movement seemed to be a renaissance of the church to return to the Bible, especially the problem of salvation (soteriology), emphasizing the supremacy of God's grace and Christ's Atonement.Marde Christian Stenly Mawikere, Perbandingan Teologi Keselamatan Antara Katolik Dan Protestan Sebelum Dan Sesudah Gerakan Reformasi. Artikel ini merupakan tinjauan perbandingan Teologi Keselamatan Antara Katolik dan Protestan Sebelum dan Sesudah Reformasi berdasarkan ulasan literatur yang telah tersedia. Berangkat dari konteks historis socio religious di Eropa sejak abad 5 sampai 1517 yang menunjukkan paduan antara filsafat dengan teologi menyebabkan gereja menyimpang dari ajaran Alkitab. Situasi kekristenan dan zeit geist abad pertengahan yang disebut abad kegelapan gereja memicu lahirnya gerakan reformasi protestan. Gerakan reformasi protestan seakan menjadi renaissance gereja untuk kembali kepada pemahaman Alkitab, terutama masalah keselamatan (soteriologi) yang menekankan supremasi anugerah Allah dan Penebusan Kristus.